Premature aging and reduced cancer incidence associated with near-complete body-wide Myc inactivation - Huabo Wang; Jie Lu; Taylor Stevens; Alexander Roberts; Jordan Mandel; Raghunandan Avula; Bingwei Ma; Yijen Wu; Jinglin Wang; Clinton Van’t Land; Toren Finkel; Jerry E. Vockley; et al. (Cell Reports, 2023)
Summary: MYC proto-oncogene dysregulation alters metabolism, translation, and other functions in ways that support tumor induction and maintenance. Although Myc+/− mice are healthier and longer-lived than control mice, the long-term ramifications of more complete Myc loss remain unknown. We now describe the chronic consequences of body-wide Myc inactivation initiated postnatally. “MycKO” mice acquire numerous features of premature aging, including altered body composition and habitus, metabolic dysfunction, hepatic steatosis, and dysregulation of gene sets involved in functions that normally deteriorate with aging. Yet, MycKO mice have extended lifespans that correlate with a 3- to 4-fold lower lifetime cancer incidence. Aging tissues from normal mice and humans also downregulate Myc and gradually alter many of the same Myc target gene sets seen in MycKO mice. Normal aging and its associated cancer predisposition are thus highly linked via Myc.